Exploring the Capacity of Organizational Citizenship Behavior in the Link of Workplace Surroundings on Employee Effectiveness - Hery Verianto The (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The effectiveness of organizations depends not only on employees’ skills but also on their individual capacities and behaviors. Organizational Citizenship Behavior (OCB) or voluntary actions beyond formal job duties plays a vital role in enhancing organizational success and creating supportive workplace surroundings. While a positive either physically or nonphysically workplace atmosphere can encourage OCB and boost employee effectiveness. The inconsistency findings of studies about how workplace surroundings relate to OCB to enhance employee effectiveness reveal the gaps on these interactions. Therefore, this research seeks to explore the capacity of Organizational Citizenship Behavior (OCB) in link of the workplace surroundings on employee effectiveness. Adopting a quantitative methodology and a causal-descriptive design, the study employs validity and reliability assessments, classical assumption testing, regression, path analysis, and the Sobel test to verify the capacity of OCB effect. This study involved all 116 employees selected through a census sampling approach, and the data were processed using SPSS version 23. The analysis results demonstrate that the workplace surroundings have a positive and significant impact on OCB, which subsequently contributes to improved employee effectiveness. Furthermore, the workplace surroundings also exert a direct impact on performance outcomes. These findings indicate that OCB functions as a partial mediator between the workplace surroundings and employee effectiveness. Although the direct impact of the workplace surroundings is more substantial than the indirect effect through OCB, the mediating role of OCB remains essential, highlighting its importance in employee selection and development initiatives within organizations.